A novel low temperature aerobic technology with electrochemistry for treating pesticide wastewater: Compliance rate, mathematical models, economic and environmental benefit analysis. (September 2021) - Yu, Liqiang; Chen, Zhaobo; Hu, Dongxue; Ge, Hui; Liu, Lixue; Liu, Zhiguo; Liu, Hongxia; Cui, Yubo; Zhang, Wanjun; Zou, Xuejun; Zhang, Ying; Zhu, Qiankun
Highlights: A novel combination system was developed to treat pesticide wastewater. Two strategies for enhancing effluent quality were proposed. Models were developed to predict the biomass per unit carrier in TVDBFB. Economic and environment analysis were proposed to evaluate two strategies. Abstract: In this study, a novel combination system of the tapered variable diameter biological fluidized bed (TVDBFB) with electrochemistry (EC) has been developed and its performances are investigated at different seasons. The results showed that the COD removal efficiency of TVDBFB increased from 61% to 67% and compliance rate increased from 84% to 88% when the carrier packing rate increased from 15% to 30% and temperature was 12 ℃. However, COD removal efficiency and compliance rate increased to 87% and 100% when EC was a post treatment unit. The mathematical models could fit well with the attached biomass, which can be applied to reflect and predict the biomass per unit carrier under different conditions, and the EC removal of COD follow the first-order reaction kinetic model. The economic and environmental benefit analysis indicated that TVDBFB and EC were feasible for treating pesticide wastewater.